Rubiaceae endémicas del Perú - Pino, Delicia (2006)
The Rubiaceae are represented in Peru by approximately 102 genera and 740 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly trees and shrubs. One genus, Stilnophyllum, is endemic to Peru. Here we recognize 96 endemic taxa in 33 genera. Endemic taxa are found mainly in Humid Lowland Amazonian Forests, Very Humid Premontane Forests and Very Humid Montane Forests regions, between 100 and 3700 m elevation. Psychotria is the genus with the largest number of endemic species, which is, at the same time, a taxonomic challenger in need of more studies. We applied IUCN categories and criteria to 49 taxa. Eleven endemic taxa have been recorded within Peru’s protected areas system.